The Influence of the Work Environment on the Work Motivation of Generation Z at Bank X - Diovanessa, Charla Bernadhetta Angeline; Dwianto, Agung Surya (Riwayat: Educational Journal of History and Humanities, 2025)
This study functions to examine the influence of the work environment on the work motivation of Generation Z at Bank X. Using a quantitative approach method with data collection techniques through the distribution of questionnaires to 35 Generation Z respondents at Bank X. Validity and reliability tests have been carried out on the research instrument, which is then analyzed using descriptive analysis and simple linear regression with the aim of testing the relationship between the work environment and work motivation. Positive and significant results are shown by the results of the study, that the work environment has an influence on the work motivation of generation Z at Bank X. Regression analysis results in the equation Y = 24.115 + 0.550X, which means that every time the quality of the work environment improves, an increase in work motivation will occur. The t-test showed a significance value of 0.028, so that the analysis appeared that there was a significant influence between the work environment on work motivation. A determination coefficient value (R) of 0.139 indicates that 13.9% of the variation in work motivation can be explained by the work environment, while the rest is influenced by other factors outside of this study.